Estimating the environmental costs and benefits of demolition waste using life cycle assessment and willingness-to-pay: A case study in Shenzhen - Wang, T.; Wang, J.; Wu, Peng; Wang, J.; He, Q.; Wang, X. (Elsevier, 2018)
© 2017 Elsevier Ltd Construction and demolition waste is one of the largest contributors to solid waste generation. Recycling is considered an effective strategy to manage construction and demolition waste; however, the environmental costs and benefits of recycling, compared with a traditional landfill strategy, have not been fully investigated. This study uses a life cycle assessment and willingness-to-pay methodology to investigate the environmental impacts of recycling 1 tonne of demolition waste in Shenzhen. The environmental impacts are global warming, ozone depletion, acidification, eutrophication, suspended particulate matter, solid waste, and land consumption. The results show that recycling can bring an environmental benefit of ¥1.21 per tonne while direct landfill leads to an environmental cost of ¥12.04 per tonne. The environmental costs and benefits of recycling concrete, brick, steel, and mortar, which are the most commonly seen types of component from demolition waste, are also investigated. The results can be used by regulatory authorities to establish strategies and policies, such as the provision of monetary incentives, in order to encourage recycling activities. The results can also be used to establish appropriate landfill charges.